Proceedings of the 51st ACM Technical Symposium on Computer Science Education 2020
DOI: 10.1145/3328778.3366815
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Prevalence of the Impostor Phenomenon Among Computer Science Students

Abstract: The Impostor Phenomenon (IP) is often discussed as a problem in the field of computer science, but there has yet to be an empirical study to establish its prevalence among CS students. One survey by the Blind app found that a high number of software engineers at some of the largest technology companies self-reported feelings of Impostor Syndrome; however, self-reporting of Impostor Syndrome is not the standard diagnostic for identifying whether an individual exhibits feelings of the Impostor Phenomenon. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…Although sense of belonging is distinct from self-efficacy [35], one can imagine how they might influence one another. Moreover, the persistence of a lack of sense of belonging with women may be connected to the recent finding of Rosenstein et al that showed women experience considerably higher rates of Imposter Phenomenon than men [25]. It could be difficult for a student to feel like they belong if they feel like an imposter.…”
Section: Discussionmentioning
confidence: 96%
“…Although sense of belonging is distinct from self-efficacy [35], one can imagine how they might influence one another. Moreover, the persistence of a lack of sense of belonging with women may be connected to the recent finding of Rosenstein et al that showed women experience considerably higher rates of Imposter Phenomenon than men [25]. It could be difficult for a student to feel like they belong if they feel like an imposter.…”
Section: Discussionmentioning
confidence: 96%
“…Considering the degree of accuracy, d = 0.05 and p as the approximate proportion of YIS (p = 0.47), taken from a related study conducted in Pakistan (Qureshi et al, 2017). So, the calculated sample size was 382; however, we targeted more subjects to be included than the required sample size.…”
Section: Survey Proceduresmentioning
confidence: 99%
“…Indeed, IS is becoming a growing public health issue both globally and regionally. For instance, the prevalence of IS among medical students has been found to be 30% in the US (Villwock et al, 2016), 45.7% in Malaysia (Ikbaal & Salim Musa, 2018, and 47% in Pakistan (Qureshi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations